Memahami Prinsip Tata Kelola Kopi Kenangan - David Sebastian Gunawan; Rasyid Tarmizi (ProBisnis : Jurnal Manajemen, 2026)
This study aims to understand the governance principles implemented by Kopi Kenangan in building a sustainable coffee-based beverage business. The main focus lies on three aspects: organizational structure, sustainability practices (ESG), product and technology innovation management, and stakeholder engagement. The literature review findings indicate that the success of Kopi Kenangan is not only determined by product innovation, but also by a strong governance system that is collaborative and responsive to market changes. By applying value-oriented and sustainability-driven good corporate governance principles, Kopi Kenangan is able to compete effectively in the highly dynamic F&B industry.